Targeting interlukin-6 to relieve immunosuppression in tumor microenvironment - Qian Liu; Shengnan Yu; Anping Li; Hanxiao Xu; Xinwei Han; Kongming Wu (Tumor Biology, 2017)
Immunotolerance is one of the hallmarks of malignant tumors. Tumor cells escape from host immune surveillance through various mechanisms resulting in tumor progression and therapeutic resistance. Interlukin-6 is a proinflammatory cytokine involved in many physiological and pathological processes by integrating with multiple intracellular signaling pathways. Aberrant expression of interlukin-6 is associated with the growth, metastasis, and chemotherapeutic resistance in a wide range of cancers. Interlukin-6 exerts immunosuppressive capacity mostly by stimulating the infiltrations of myeloid-derived suppressor cells, tumor-associated neutrophils, and cancer stem-like cells via Janus-activated kinase/signal transducer and activator of transcription 3 pathway in tumor microenvironment. On this foundation, blockage of interlukin-6 signal may provide potential approaches to novel therapies. In this review, we introduced interlukin-6 pathways and summarized molecular mechanisms related to interlukin-6-induced immunosuppression of tumor cell. We also concluded recent clinical studies targeting interlukin-6 as an immune-based therapeutic intervention in patients with cancer.